Labour law beyond national borders - Aimo, Mariapaola (Delavci in delodajalci, 2019)
The present article will provide an overview - the sixth of its kind since 2013, when the first "edition" was published by Lavoro e diritto and Revue de Droit comparé du Travail et de la Sécurité sociale - on the main topics analysed in the majority of the journals belonging to the International Association of Labour Law Journals (IALLJ)1 throughout 2017. More specifically, the article reviews the issues addressed in twenty-four out of the Association's thirty member journals. The remaining journals were not examined chiefly because of accessibility or language barriers2. As regards the subjects selected for consideration, the authors decided to focus on three topic groups that reflect the major interests shown by IALLJ scholars in the large number of articles under review. This overview is thus divided into three sections: 1) Towards an inclusive working society?; 2) The transformations of work: new challenges and new risks "test" the law; 3) Perspectives for collective labour law.
Keywords: collective labour law; delo; delovno pravo; digitalizacija; digitalization; kolektivno delovno pravo; labour law; precariousness; prekarnost; work